2017
DOI: 10.1002/macp.201700273
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent ROMP Monomers and Copolymers for Biomedical Applications

Abstract: The synthesis and characterization of a series of green‐, blue‐, and red‐fluorescent exo‐oxanorbornene acid and imide monomers carrying nitrobenzofurazan, coumarin, and rhodamin B, respectively, as fluorophores are presented. These monomers carry oxanorbornene as polymerizable unit, and are readily copolymerized with bioactive functional oxanorbornene monomers by ring‐opening metathesis polymerization, as demonstrated by gel permeation chromatography and NMR spectroscopy. Due to the ease of synthesis of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…UV irradiation of these units trigger C,H‐insertion reactions with neighboring polymer segments, so that homogeneously crosslinked poly(guanidinium oxanorbornene) layers were obtained . Since it is analytically difficult to prove layer shedding from a polymer multilayer stack, the basic crosslinkable poly(guanidinium oxanorbornene) polymer 1 (Figure a) was further modified with different fluorescent groups: with the green‐fluorescent nitrobenzoxadiazol ( 1a , Figure a), the red‐fluorescent rhodamine B ( 1b , Figure a), and the blue‐fluorescent coumarin group ( 1c , Figure a) . Using these fluorescent labels, different antimicrobial layers in the same multilayer stack could be unanimously detected by fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…UV irradiation of these units trigger C,H‐insertion reactions with neighboring polymer segments, so that homogeneously crosslinked poly(guanidinium oxanorbornene) layers were obtained . Since it is analytically difficult to prove layer shedding from a polymer multilayer stack, the basic crosslinkable poly(guanidinium oxanorbornene) polymer 1 (Figure a) was further modified with different fluorescent groups: with the green‐fluorescent nitrobenzoxadiazol ( 1a , Figure a), the red‐fluorescent rhodamine B ( 1b , Figure a), and the blue‐fluorescent coumarin group ( 1c , Figure a) . Using these fluorescent labels, different antimicrobial layers in the same multilayer stack could be unanimously detected by fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of the fluorescent and nonfluorescent antimicrobial poly(guanidinium oxanorbornenes) shown in Figure was performed in analogy to previously reported similar polymers and is described in Section of the Supporting Information. In short, the respective monomers (Figure S1, Supporting Information) where mixed in the appropriate ratios and polymerized in dichloromethane using Grubbs' 3rd generation catalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports that have been published on quaternary ammonium‐based antibacterial polymers . For polymer design, ring opening metathesis polymerization (ROMP) is one of the important techniques for the preparation of well‐defined water‐soluble polymer architectures and biologically active polymers . Ilker et al studied ammonium‐based polymers derived via ROMP and they found that antibacterial and hemolytic activity strongly depends on the length of alkyl substituent of the repeating units .…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49] For polymer design, ring opening metathesis polymerization (ROMP) is one of the important techniques for the preparation of well-defined water-soluble polymer architectures [37,38,[50][51][52] and biologically active polymers. [53][54][55][56] Ilker et al studied ammonium-based polymers derived via ROMP and they found that antibacterial and hemolytic activity strongly depends on the length of alkyl substituent of the repeating units. [57] The Tew group also reported that the polymer bearing the guanidine functionality is more selective.…”
mentioning
confidence: 99%